PEMANFAATAN PUPUK LIMBAH AGAR-AGAR TERHADAP PERTUMBUHAN SEMAI MAHONI (Swietenia macrophylla, King) DI MEDIA TAILING TAMBANG EMAS PT ANTAM UBPE PONGKOR - PIPIH SUPTIJAH; BASUKI WASIS; AYU BABY MUTIARA MANDELLA (Akuatik: Jurnal Sumberdaya Perairan, 2011)
The processing of agar produces 65-70% residu from all raw materials that are used. The residu in form of drugs or solid waste contain macro and micro nutrients which unfortunately have not been used optimally. The waste has a potential to use as an organic fertilizer. The effect of agar waste on growth of mahogany seed and physical and chemical properties of tailing were studied. Compost fertilizer was used as comparison to see the effectiveness of addition agar waste on growth of mahogany. The growth of mahogany seed was observed from height and diameter parameter, while the minerals content were measured by Atomic Absorption Spectrophotometry (AAS). The result shown thar the highest growth was achieved when mahogany was treated with 1% agar waste, while the biggest diameter was achieved with 1,5% agar waste. Agar waste treatment improved chemical properties of tailing but has not significant change on physical properties.